Handbook of research on learning design and learning objects issues, applications, and technologies - Lockyer, Lori. (Hershey, PA : Information Science Reference, 2009)
'This book provides an overview of current research and development activity in the area of learning designs'--Provided by publisher.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Instructional systems -- Design; Educational technology; Educational innovations; Electronic books